Cambodia and Asian Development Bank partnership for inclusive growth development effectiveness brief. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It explores how ADB interventions have made a difference in the lives of people in the country. Over the past 20 years, Cambodia has achieved remarkable economic development, attaining middle income status in 2016 and reducing poverty rate from 47.8% in 2007 to 13.5% in 2014. As Cambodia largest multilateral development partner, ADB completed projects between 2011 and 2017 have provided low cost electricity, improved water supply, and delivered new or improved sanitation to thousands of rural households, and constructed or upgraded more than 1,400 kilometers of roads.
Keywords: Inclusive growth -- Cambodia; Poverty alleviation -- Cambodia; Electronic book